Polygamy In The Duchess Movie Directed By Saul Dibb (2008): A Feminist Approach - Yudistira, Arif Saifudin, Dr.Phil. Dewi Candraningrum, M.Ed, Nur hidayat S.Pd (2013)
The study is proposed to analyze the polygamy in the Duchess Movie by Feminist Approach. The objectives study are: The first is to analyze the structural elements of Duchess Movie and the second is to analyze the influence of polygamy to the main character (Georgiana) in the Duchess Movie based on the feminist approach. The study is qualitative study using The Duchess Movie as object of the study. There are two kinds of data source: primary and secondary. The primary data source is The Duchess Movie (2008), the secondary data source are books, a script, the movie responses, the official web "the duchess movie", and the other related to the subject. The method of collecting data in the research is library research by summarizing, paraphrasing, and documenting the data. In analyzing the data, the researcher employs descriptive analysis. The result of the study is as follows: first, the Duchess Movie wants to illustrate how women are subordinate in patriarchal society and man as super ordinate. Second, in this movie Georgiana as the major character in this movie wants to say that women need to struggle in getting the rights in their life, and women rights are not given but must be struggle it for. The last is Georgiana speaking against patriarchal system concept of women. It can be seen when she rebels against the type of women position, role, rights, and participation.